A prospective international Aspergillus terreus survey: an EFISG, ISHAM and ECMM joint study. (October 2017) - Risslegger, B.; Zoran, T.; Lackner, M.; Aigner, M.; Sánchez-Reus, F.; Rezusta, A.; Chowdhary, A.; Taj-Aldeen, S.J.; Arendrup, M.C.; Oliveri, S.; Kontoyiannis, D.P.; Alastruey-Izquierdo, A.; et al.
Abstract: Objectives: A prospective international multicentre surveillance study was conducted to investigate the prevalence and amphotericin B susceptibility of Aspergillus terreus species complex infections. Methods: A total of 370 cases from 21 countries were evaluated. Results: The overall prevalence of A. terreus species complex among the investigated patients with mould-positive cultures was 5.2% (370/7116). Amphotericin B MICs ranged from 0.125 to 32 mg/L, (median 8 mg/L). Conclusions: Aspergillus terreus species complex infections cause a wide spectrum of aspergillosis and the majority of cryptic species display high amphotericin B MICs.